(untitled) (ENTHYMEMA, 2012)
Exploitation films from the 1970s and early 80s such as Foxy Brown (Jack Hill, 1974) and Switchblade Sisters (Jack Hill, 1975) were the first films to allow women to actively control the narrative and course of events in a film. Men become secondary characters who had no or little control over the course of events in these films. Because the films were made during the rapidly changing social climate of the 1970s, the films also became a barometer in their treatment of female characters of social mores. Director Quentin Tarantino’s films Death Proof (2007), Kill Bill I and II (2003 and 2004), Jackie Brown (1997), and Inglourious Basterds (2009) attempt to modernize the active women from exploitation films of the 1970s, reworking the female characters’ mobilization against typical gender roles, and attributing her with the abilities to compete, and even challenge men in a patriarchic society.However, Tarantino’s films mostly fail to progress beyond the trappings of the classic exploitation films of the 1970s, still relying heavily on the excessive display of female bodies, and subjugating women to the male camera and spectator gaze. In Tarantino’s attempt to remove female characters from the gender restraints of most Hollywood films, he creates the female action star, and inadvertently reverses the work of classic exploitation films by limiting the traits strong women are able to possess. By contrast, the female leads of 1970s exploitation films, although still heavily sexualized, are able to be physically powerful while retaining their feminine identifications as a wives, mothers, lovers, and beauty queens. Tarantino’s portrayal of strong women is more limited, however when strong sexuality and typical feminine traits are not connected to the powerful female characters. Instead female sexuality and feminine appearances are shown as weaknesses that contribute to the female characters’ deaths or lack of individuality. Tarantino allows one other female character, a strong warrior who takes on an action star role and becomes powerful through her rejection of feminine traits.